La face cachée des églises restaurées :des questions d’authenticité / Reading The hidden face of restored churches: questions of authenticity - Bruno Phalip (Anastasis: Research in Medieval Culture and Art, 2017)
Restoring medieval churches is a requirement of our times – therefore the restoration practices of the 19th and the 20th are now material for scholarly research. But caution and limitations are imperative. A reflexion must be conducted about the quality of the restorations, and about their impacts. Finally, the maintenance of the building itself must be possible, without heavy-handed interventions or ill-considered cleaning. Examples from France and Cyprus are studied here.